2015
DOI: 10.1038/ncomms9815
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Kv1 and Kv7 enhances neuronal excitability during structural axon initial segment plasticity

Abstract: Structural plasticity of the axon initial segment (AIS), the trigger zone of neurons, is a powerful means for regulating neuronal activity. Here, we show that AIS plasticity is not limited to structural changes; it also occurs as changes in ion-channel expression, which substantially augments the efficacy of regulation. In the avian cochlear nucleus, depriving afferent inputs by removing cochlea elongated the AIS, and simultaneously switched the dominant Kv channels at the AIS from Kv1.1 to Kv7.2. Due to the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
101
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(114 citation statements)
references
References 54 publications
9
101
2
Order By: Relevance
“…These discrepancies might be due to differences in cell types, species, strain, or experimental procedures, including the kind of antibodies or fixation conditions. For example, in the avian nucleus magnocellularis neurons, K v 7.2 immunoreactivity was distributed along the entire AIS (50). In agreement with our findings and in line with previous work (38,39), FGF14, which physically bridges the K v 7 and Na v channels and entirely localizes to the proximal AIS (38,39), exhibited a shorter length than that of ankyrin G (∼24 μm versus 33 μm) in our preparation (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…These discrepancies might be due to differences in cell types, species, strain, or experimental procedures, including the kind of antibodies or fixation conditions. For example, in the avian nucleus magnocellularis neurons, K v 7.2 immunoreactivity was distributed along the entire AIS (50). In agreement with our findings and in line with previous work (38,39), FGF14, which physically bridges the K v 7 and Na v channels and entirely localizes to the proximal AIS (38,39), exhibited a shorter length than that of ankyrin G (∼24 μm versus 33 μm) in our preparation (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…To rapidly produce large inward and outward currents mediating the AP, the AIS contains a complex arrangement of cytoskeletal and transmembrane proteins clustering high densities of voltage-gated sodium (Nav) and potassium (Kv) channels in the axolemma (2)(3)(4). Although the composition of ion channels is critical for initiation and regulation of firing patterns, there are emerging insights that the AIS is not operating in isolation but is also subject to activity-dependent changes in size and location constrained by the local dendritic branch geometry and the passive cable properties (5)(6)(7). Experimental studies linking changes in AIS length and neuronal output showed that an increased length facilitates AP generation (6,8).…”
mentioning
confidence: 99%
“…1,61,76 The tuning of the action potential threshold is critically dependent on the activity of voltage-gated calcium channels and the density and kinetic properties of Na V and K V channels. 1,77 Crucial questions, such as how channels are inserted into and removed from membranes and whether there are density gradients in Na v and K v channel expression along the AIS, can now be answered with the observation of channel dynamics in the membrane. Interestingly, both ion channel populations (Na V and K V ) are linked to the Ankyrin G scaffold via similar binding motifs.…”
Section: Na V Channelsmentioning
confidence: 99%
“…18 Alterations to ion channel composition and AIS size are known mechanisms of neuronal excitability tuning. 1,77 It remains to be explored whether the surface dynamics of Na V and K V channels contribute to such alterations in AIS size or position.…”
Section: Na V Channelsmentioning
confidence: 99%
See 1 more Smart Citation